Transient Effects in Atmosphere and Ionosphere Preceding the 2015 M7.8 and M7.3 Gorkha–Nepal Earthquakes - Ouzounov, Dimitar; Pulinets, Sergey; Davidenko, Dmitry; Rozhnoi, Alexandr; Solovieva, Maria; Fedun, Viktor; Dwivedi, B. N.; Rybin, Anatoly; Kafatos, Menas; Taylor, Patrick (Frontiers in Earth Science, 2021)
We analyze retrospectively/prospectively the transient variations of four different physical parameters in the atmosphere/ionosphere during the M7.8 and M7.3 earthquakes in Nepal, namely: (i) thermodynamic proprieties in the lower atmosphere; (ii) outgoing earth radiation (OLR) at the TOA; (iii) GPS/TEC and (iv) the very-low-frequency (VLF/LF) signals at the receiving stations in Bishkek (Kyrgyzstan) and Varanasi (India). We found that in mid-March 2015, there was a rapid increase in the increase in radiation from the atmosphere observed by satellites. This anomaly was located close to the future M7.8 epicenter and reached a maximum on April 21-22. The GPS/TEC data analysis indicated an increase and variation in electron density, reaching a maximum value during April 22-24. A strong negative TEC anomaly in the crest of EIA (Equatorial Ionospheric Anomaly) occurred on April 21, and a strong positive anomaly was recorded on April 24, 2015. The behavior of VLF-LF waves along NWC-Bishkek and JJY-Varanasi paths has shown abnormal behavior during April 21-23, several days before the first, stronger earthquake. Our continuous satellite OLR analysis revealed this new strong anomaly on May 3, which was why we anticipated another significant event in the area. On May 12, 2015, an M7.3 occurred. Our results show coherence between the appearance of these pre-earthquake transient’s effects in the atmosphere and ionosphere (with a short time-lag, from hours up to a few days) and the occurrence of the 2015 M7.8 and M7.3 events in Nepal. The spatial characteristics of the pre-earthquake anomalies were associated with a large area but inside the preparation region estimated by Dobrovolsky-Bowman. The pre-earthquake nature of the signals in the atmosphere and ionosphere was revealed by simultaneous analysis of satellite, GPS/TEC, and VLF/LF observations and suggest that they follow a general temporal-spatial evolution pattern been seen in other large earthquakes worldwide.